2020
DOI: 10.22329/csw.v21i1.6224
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Animals as an Important Part of Helping

Abstract: The beneficial role of companion animals on human health and wellbeing across the life span is well documented in the rapidly expanding multi disciplinary body of literature known as human animal interactions (HAI). Social workers practice at the interface of people and their diverse environments. The presence of human animal bonds (HAB) within client systems, between people and companion animals in particular, are increasingly acknowledged and valued by social workers. Additionally, some social workers incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 112 publications
(170 reference statements)
0
4
0
1
Order By: Relevance
“…The institution has a capacity of 582 medium-risk prisoners and 122 minimum-risk prisoners (Correctional Service Canada, 2017). Drumheller's canine-assisted learning and wellness program for substance use, PAWSitive Support, is an intensive 3.5-day (28-hour) program that focuses on participants' connections and bonds with the program dogs (Chalmers et al, 2023). The program was designed for those serving life sentences and who had unintentionally overdosed in the facility.…”
Section: El As a Conceptual Approach To Canine-assisted Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The institution has a capacity of 582 medium-risk prisoners and 122 minimum-risk prisoners (Correctional Service Canada, 2017). Drumheller's canine-assisted learning and wellness program for substance use, PAWSitive Support, is an intensive 3.5-day (28-hour) program that focuses on participants' connections and bonds with the program dogs (Chalmers et al, 2023). The program was designed for those serving life sentences and who had unintentionally overdosed in the facility.…”
Section: El As a Conceptual Approach To Canine-assisted Learningmentioning
confidence: 99%
“…In turn, they reflected on how they had treated others in the past (including dogs and humans) related to of their addiction and mental health issues and discussed changing their behaviors in the future. Thus, there may be other ways that prisons can draw on human–animal interaction in substance use programming, including information about participants' own pets (Chalmers et al, 2020; Hanrahan & Chalmers, 2020). For example, a pet query is a simple question that asks about current or previous pets in the household (Hodgson et al, 2017).…”
Section: Implications For Clinical Forensic Nursing Practicementioning
confidence: 99%
“…Der Anspruch, Tiere in die Betrachtung und Hilfeplanung zu integrieren, wird auch in der Sozialarbeit formuliert 20 21 22 26 27 28 29 30 . Ein erster Schritt wäre es, bei der Suchtanamnese systematisch zu erfassen, ob Tiere gehalten werden, so dass im weiteren Verlauf auch dieses Thema regelmäßig aufgerufen und reflektiert werden kann.…”
Section: Diskussionunclassified
“…Bretzlaff-Holstein 2018indicates that attention to animals in social work practice and education is limited and has largely focused on the social and therapeutic benefits of the human-animal bond/partnerships (Risley-Curtiss, 2010), the relationship between animal cruelty and family violence (Adamson & Darroch, 2016;Walker, Aimers, & Perry, 2015), how animals feature in the context of disasters (see Adamson & Darroch, 2016) and attention to grief and loss (see Arkow, 2020). Chalmers, Dell, Dixon, Dowling, and Hanrahan (2020) argue that, while attention to human-animal relations is gaining traction for social work educators, researchers and practitioners, there is not yet the education and training in place to support this growing area of interest. Moreover, Hanrahan (2013) found that, while social workers have an awareness of the value of human-animal relations, either this is largely ignored in practice or practitioners are including animals in their practice but without specific training to do so.…”
Section: The Social Work Programme Contextmentioning
confidence: 99%